313 Passive Flow-Reversal With Balloon-Guide Catheter for Transfemoral Carotid Artery Stenting: Proof of Concept, Technical Description and Experience. (April 2023) - Monteiro, Andre; Cappuzzo, Justin Mark; Waqas, Muhammad; Lim, Jaims; Baig, Ammad; Khawar, Wasiq; Popoola, Daniel; Davies, Jason; Siddiqui, Adnan Hussain; Levy, Elad I.; Snyder, Kenneth Vincent
Abstract : INTRODUCTION: The use of modern transfemoral balloon guide catheters (BGC) for flow reversal during carotid artery stenting (CAS) is scarcely described in literature but represents a promising and efficient technique for embolic protection. METHODS: We performed a retrospective analysis of patients ≥ 18-year-old who underwent elective CAS with the use of flow-reversal through the Walrus BGC. The BGC is positioned in the common carotid artery and inflated, followed by opening of the stop-cock for passive reversal of flow. We utilized a robotic transcranial Doppler monitoring during this technique for proof of concept. Patients' characteristics, procedural details and clinical follow-up were evaluated. RESULTS: One-hundred and ten patients were included. Mean age was 69.1 years ± SD 9.6 and 30 (27.3%) were female. Most common comorbidities were hyperlipidemia (81.8%) and hypertension (73.6%). 54 (49.1%) patients were symptomatic. 102 (92.7%) patients had stenosis ≥70%. Contralateral stenosis ≥50% was present in 54 (49.1%) patients. Distal filters were used in 91 (82.7%) cases. Angioplasty was performed in 86 (78.2%) patients. Stenting was successful in 100% of cases. There were no periprocedural TIA or stroke. Stroke or TIA and mortality were both observed in only two (1.8%) patients during 30-days follow-up, of which one was due to non-compliance with antiplatelet regimen. CONCLUSIONS: In our institution's experience, this technique was safe, feasible and efficient, with 100% technical success and no periprocedural thromboembolic complications. More extensive studies are needed to establish the role of proximal protection with flow-reversal using modern BGCs.